The Outcome of Cell Therapy Treating Urinary Incontinence Correlates with Precise Cell Localization in the Sphincter Complex - Niklas Harland; Liv Johnen; Kamal T. Avula; Andrea Buzanich-Ladinig; Lukas Schwarz; Jasmin Knoll; Arnulf Stenzl; Wilhelm K. Aicher (Biomedicines)
Background/Objectives: Urethral sphincter muscle deficiency is the leading cause of stress urinary incontinence. Preclinical and clinical studies suggested that cell therapy may improve the situation. However, the overall efficacy of cell therapies did often not satisfy the patient’s needs. We, therefore, investigated in a large animal model of incontinence if the localization of injected regenerative cells in the deficient urethral sphincter muscle correlated with the outcome. Methods: Urethral sphincter insufficiency was induced in three cohorts of pigs and confirmed by urodynamics. Then, either myogenic progenitor cells (MPCs) or adipose tissue-derived stromal cells (ADSCs) were injected into the injured sphincter complex by Williams needle under visual using a cystoscope. Sham-treated animals served as controls. Functional sphincter muscle regeneration was monitored by urodynamics over 5 weeks of follow-up. The localization of the injected cells was investigated by histology of cryosections of the tissue targeted. Results: Injection of MPCs near the sphincter muscle yielded better functional recovery when compared to MPC injections in adjacent sides. By contrast, injection of ADSCs in the submucosal tissue adjacent to the muscle led to better regeneration when compared to ADSC injections into the sphincter muscle. After five weeks of follow-up, MPCs yielded an overall robust but not significant improvement when compared to mock-treated controls, while ADSC injections reached significance. Conclusions: This small proof-of-principle study suggests that the clinical outcome of cell therapy for urinary incontinence depends on the choice of therapeutic cells and the precise localization of the cells in the tissue targeted as well.